Decreased Aviation Leads to Increased Ice Crystal Number and a Positive Radiative Effect in Cirrus Clouds. Issue 2 (4th April 2022) - Zhu, Jialei; Penner, Joyce E.; Garnier, Anne; Boucher, Olivier; Gao, Meng; Song, Lei; Deng, Junjun; Liu, Cong‐qiang; Fu, Pingqing
Abstract: Travel restrictions in the wake of the COVID‐19 pandemic resulted in an unprecedented decrease of 73% in global flight mileage in April–May 2020 compared to 2019. Here we examine the CALIPSO satellite observations and find a significant increase in ice crystal number concentrations (Ni) in cirrus clouds in the mid‐latitudes of the Northern Hemisphere, which we attribute to an increase in homogeneous freezing when soot from aircraft emissions is reduced. A relatively small positive global average radiative effect of 21 mW m −2 is estimated if a decrease in aircraft traffic continues, with an average of up to 64 mW m −2 over the area where aviation is most active. We infer from this analysis that the worldwide adoption of biofuel blending in aircraft fuels that lead to smaller soot emissions could lead to a significant change in the microphysical properties of cirrus clouds but a rather small positive radiative effect. Plain Language Summary: Cirrus clouds play an important role in the Earth's radiation budget. Whether soot from aircraft emissions would change the property of large‐scale cirrus clouds has been a critical question. We show that the unprecedented decrease in aircraft traffic as a result of the COVID‐19 pandemic leads to a significant increase in ice crystal number as detected by satellite. An increase in ice crystal number and positive radiative effect is estimated using a state‐of‐the‐science earth system model if the reduction in aviation activity continues for the foreseeable future. As adoption of blending biofuel in the aviation sector would lead to similar reductions (50%–70%) of aircraft soot emissions in the future, remarkable changes in the microphysical properties of large‐cirrus clouds and positive radiative effects can be expected relative to a case with no biofuel blending. Key Points: A significant increase in the number of ice crystals in cirrus clouds was found due to the decreased aircraft soot emission The increased ice crystal number can be explained by an enhancement of homogeneous freezing due to the decreased ice nuclei particles Worldwide adoption of biofuel blending could lead to a significant change in the microphysical properties of cirrus clouds in the future